Development of biomimetic sensors to determine the functionality of in vitro cell models - Frangež, Matjaž (Anali PAZU, 2024)
Advances in biomedical science have enabled the development of in vitro models that mimic human tissues. Non-invasive real-time monitoring of these models would provide valuable insights without disrupting the cellular environment. This study explores the use of molecularly imprinted polymers (MIPs) for this purpose, focusing on insulin and lactate as biomarkers of cellular metabolism. MIP sensors were created by electropolymerizing pyrrole around insulin or lactate templates on carbon electrodes. The sensors showed high sensitivity and selectivity, with detection ranges of 20.0–70.0 pM for insulin (LOD: 2.41 pM) and 0.5–3.0 mM for lactate. These findings highlight MIPs’ potential for personalized diagnostics and therapy monitoring.
Keywords: biomimetic sensors; biomimetični senzorji; insulin; inzulin; MIP sensor; MIP senzor; molecular imprinting; molekularno vtiskanje; polipirol; polypyrrole matrix